Diversity and ecology of Varanus indicus in Pepaya Island at Teluk Cenderawasih National Park, West Irian Jaya - DENY ANJELIUS IYAI; FREDDY PATTISELANNO (Society for Indonesian Biodiversity, 2006)
Monitor lizard (Varanidae) has dispersed widely in Indonesia, even in Papua. Papua contents of six species. It’s distribution, abundance, both in land and island have been known yet, even carrying capacity of feeding relative limited. However, species extinction rates in nature were increasing both in it. This research was done in Papaya Island in Teluk Cenderawasih National Park, Nabire, Papua since 24th -25th October 2005. Descriptive method was done to answer this study. This research resulted that in Papaya island contents only one species that is Varanus indicus. The V. indicus chosen same habitat in southern part of Papaya island. This species dispersed on 0-4 m above sea level, humidity about 78.6%, and temperature about 23.90C. Vegetation was dominated by coconut (Cocos nucifera), bitangur (Calophyllum inophyllum) and tikar (Pandanus sp.), papaya (Carica papaya, and ketapang (Terminalia catappa). V. indicus chosen Megapodius reinwadt nest as nesting area. Population of V. indicus was estimated as much 36.3 ≈ 36 pieces by King Method. The nest of V. indicus placed in Cassuarina sp. tree where cutting down. The diet of V. indicus was found such as megapods, sea birds, lizard (sauria), butterflies and bats (Macrochyroptera). People were caused threatened both direct and indirect toward the V. indicus existence. © 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: diversities, ecology, Varanus indicus, Papaya island, Nabire, Papua.